2021
DOI: 10.7759/cureus.18296
|View full text |Cite
|
Sign up to set email alerts
|

Worsening Lower Jaw Swelling and Pain in a Teenager: Differential Diagnosis and Management

Abstract: Giant cell granuloma is a rare, benign non-neoplastic, aggressive tumor that originates mainly from the maxilla and mandible. It affects all age groups and is more commonly seen in children. We describe a 17year-old female that presented to the Pediatrics Emergency room with a history of right lower jaw pain. Examination revealed a bone-like buccal vestibular swelling on the lower right tooth, a bone-like lingual swelling, and a pink gingival overgrowth lesion. The biopsy of the lesion revealed a central giant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
2
1
0
Order By: Relevance
“…4 ). 11 12 13 14 The same radiographic features have also been reported in other giant cell lesions such as giant cell tumors and brown tumors of hyperparathyroidism. 14 In a systematic review, Stavropoulos and Katz 11 showed that 53% of all central giant cell granulomas had scalloped margins.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…4 ). 11 12 13 14 The same radiographic features have also been reported in other giant cell lesions such as giant cell tumors and brown tumors of hyperparathyroidism. 14 In a systematic review, Stavropoulos and Katz 11 showed that 53% of all central giant cell granulomas had scalloped margins.…”
Section: Resultssupporting
confidence: 66%
“… 11 12 13 14 The same radiographic features have also been reported in other giant cell lesions such as giant cell tumors and brown tumors of hyperparathyroidism. 14 In a systematic review, Stavropoulos and Katz 11 showed that 53% of all central giant cell granulomas had scalloped margins. The presence of scalloped margins in this entity has also been reported by Kahlon et al 14 In addition, they also pointed out that this radiographic feature can be seen in giant cell granulomas associated with genetic disorders such as Noonan syndrome, neurofibromatosis, cherubism, and arteriovenous malformations.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation